2019
DOI: 10.3389/fpsyg.2019.01749
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Reverberation Does Not Increase Subjective Fatigue, Subjective Listening Effort, or Behavioral Listening Effort in School-Aged Children

Abstract: Background noise and reverberation levels in typical classrooms have negative effects on speech recognition, but their effects on listening effort and fatigue are less well understood. Based on the Framework for Understanding Effortful Listening, noise and reverberation would be expected to increase both listening effort and fatigue. However, previous investigations of the effects of reverberation for adults have resulted in mixed findings. Some discrepancies in the literature might be accounted for by methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 79 publications
3
23
0
1
Order By: Relevance
“…First, we observed that SNR, which corresponded to Target level in the accented condition, had opposite effects on self-assessed effort ratings across the two conditions. We interpret this finding as consistent with the growing consensus that, when asked to rate effort levels, listeners may be evaluating different subjective qualities of the task and/or their task-related internal state in response to different kinds of challenges (Picou et al, 2019 ), and thus listeners’ responses may have been addressing or affected by different properties of the task in the two conditions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…First, we observed that SNR, which corresponded to Target level in the accented condition, had opposite effects on self-assessed effort ratings across the two conditions. We interpret this finding as consistent with the growing consensus that, when asked to rate effort levels, listeners may be evaluating different subjective qualities of the task and/or their task-related internal state in response to different kinds of challenges (Picou et al, 2019 ), and thus listeners’ responses may have been addressing or affected by different properties of the task in the two conditions.…”
Section: Discussionsupporting
confidence: 88%
“…One concern in the study of listening effort is that various measures may reflect something other than, or in addition to, the engagement of cognitive resources, especially internal assessments of performance (Picou et al, 2019 ) or affective response to task conditions or demands (Francis and Love, 2020 ). In addition, recent research demonstrates that self-report and physiological measures of listening effort may not, in fact, be reflecting the same underlying processes, or at least not doing so to the same degree (Alhanbali et al, 2019 ; Lau et al, 2019 ; Strand et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech understanding and listening effort are related, yet distinct concepts as people with hearing loss often complain that listening is tiring and effortful even when speech is audible, and words are recognized correctly ( Pichora-Fuller et al., 2016 ). Furthermore, some factors affect listening effort and not speech recognition (e.g., digital noise reduction; Sarampalis et al., 2009 ) or affect recognition but not listening effort (e.g., reverberation; Picou et al., 2019a ). Therefore, examining listening effort in addition to speech understanding can be of clinical importance, especially for school-aged children.…”
Section: Listening Effortmentioning
confidence: 99%
“…Compreender a fala em ambientes acústicos ruidosos é uma tarefa complexa e que exige maior esforço 5 . Durante o esforço auditivo, é necessário a ativação de diversos recursos cognitivos responsáveis pelo processamento e interpretação da informação auditiva, maiores níveis de atenção e memória, e uma interação dinâmica entre o processamento por meio das vias descendentes (top-down) e ascendentes (bottom-up) 6,7,8 .…”
Section: Introductionunclassified